Synaptic transmission and graded potentials - Sevigny, Charles (Henry Stewart Talks, 2023)
Types of neurotransmitters and their receptors, Action potentials, Graded potentials, Synaptic transmission, Neuromuscular junction, The distance from axon hillock, Spatial summation, Temporal summation, EPSPs and IPSPs